MEWUJUDKAN GOOD GOVERNANCE MELALUI REFORMASI BIROKRASI UNTUK MENINGKATKAN PELAYANAN PUBLIK - Purba, Debora (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Bureaucratic reform is a crucial step in achieving progress for a country or organization. Through bureaucratic reform, the governance system or organization is restructured to be not only effective and efficient but also capable of serving as the backbone of an organization's life. This paper will examine how to realize good governance through bureaucratic reform to improve public services. This study uses qualitative research with a descriptive approach. The data used in this study is secondary. The results of this paper conclude that good governance essentially requires the involvement of all stakeholders, and good governance is expected to provide solutions to all problems in governance.